2010
DOI: 10.1007/978-3-642-14165-2_29
|View full text |Cite
|
Sign up to set email alerts
|

Max-min Online Allocations with a Reordering Buffer

Abstract: Abstract. We consider online scheduling so as to maximize the minimum load, using a reordering buffer which can store some of the jobs before they are assigned irrevocably to machines. For m identical machines, we show an upper bound of Hm−1 + 1 for a buffer of size m − 1. A competitive ratio below Hm is not possible with any finite buffer size, and it requires a buffer of sizeΩ(m) to get a ratio of O(log m). For uniformly related machines, we show that a buffer of size m + 1 is sufficient to get an approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Additionally, we showed close bounds on the poa for the complete set of games, namely, that it is at least 1.691 and at most 1.7. For small numbers of machines we showed that poa(2) = poa(3) = 3 2 and poa(4) = 13 8 . In contrast to these results, we can show that for uniformly related machines even the pos for the complete set of instances is unbounded.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, we showed close bounds on the poa for the complete set of games, namely, that it is at least 1.691 and at most 1.7. For small numbers of machines we showed that poa(2) = poa(3) = 3 2 and poa(4) = 13 8 . In contrast to these results, we can show that for uniformly related machines even the pos for the complete set of instances is unbounded.…”
Section: Introductionmentioning
confidence: 86%
“…[4,2,6,8]). Various game-theoretic aspects of max-min fairness in resource allocation games were considered, but unlike the makespan minimization problem for which the poa and the pos were extensively studied (see [17,3,18]), these measures were not previously considered for the uncoordinated machine covering problem in the setting of selfish jobs and uniformly related machines.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of an objective function is to maximize the minimum load on any machine. Epstein, Levin, and van Stee [16] give a comprehensive study of the use of reordering buffers for this max-min objective function.…”
Section: Further Researchmentioning
confidence: 99%
“…Further publications are concerned with a polynomial-time approximation scheme (PTAS) (cf. Woeginger 1997) and on-line as well as semi-on-line versions of P||C min (cf., e.g., Azar and Epstein 1998;He and Tan 2002;Luo and Sun 2005;Ebenlendr et al 2006;Cai 2007;Tan and Wu 2007;Epstein et al 2011). The sole publication devoted to exact solution procedures is due to Haouari and Jemmali (2008).…”
Section: Introductionmentioning
confidence: 98%